REFLECTION ON THE REVISION OF THE BOOK OF THE LAW OF CRIMINAL LAW AND LAW OF CRIMINAL PROCEDURE OF INDONESIA - Mas, Marwan (Journal of Humanity, 2014)
The Principle of the plan revision or amendment Of the Criminal Law Act and LAW No. 8 of 1981 on the law of criminal procedure (Criminal Code) is something that necessarily, because a number of judgments were not in accordance with the conditions of the present. Criminal Code which came into effect in 1915 during colonial times, many judgments which are not in line with peoples lives today. For example, the ban showed, offering, or broadcast a preventive tool is pregnant, regulated in article 534 Criminal Code, although that provision had never been repealed as opposed to family planning programs. Its just that, those changes also should look at the reality of the needs of the community, particularly on corruption eradication efforts which should not be weakened. One of the crucial second revision of draft laws that are a number of provisions which could potentially undermine the spirit of the eradication of corruption, including the weakening of the authority of the corruption eradication Commission (KPK) in dealing with corruption cases.